Explaining the challenges of Iranian caregivers in provision of home health care to spinal cord injury patients: a qualitative study - Nasrin Galehdar; Heshmatolah Heydari (BMC, 2024)
Abstract Background The incidence of spinal cord injury (SCI) is increasing across the globe. The caregivers of patients with spinal cord injuries experience many problems during providing care to these patients. Identifying the problems experienced by caregivers can facilitate the process of care provision to these patients. So, the aim of this study was to explore the challenges of caregivers in provision of home health care to SCI patients. Methods This study was conducted by qualitative description approach in Iran from Apr 2021 to Dec 2022. The participants included the caregivers of SCI patients recruited by purposive sampling. The data were collected by face-to-face interviews and analyzed using the method proposed by Lundman and Graneheim. Results Two themes emerged from the data analysis, including burnout (with the categories of physical challenge and psychological challenges) and coping strategies (with the categories of social support and professional support). Conclusion Resolving the obstacles and problems faced by home caregivers can improve the circumstances of care provision so that they can be relieved of their own physical and psychological conundrums and deliver suitable home care to SCI patients. Trial registration number Not applicable.